Longitudinal associations of flare and damage accrual in patients with systemic lupus erythematosus - Rangi Kandane-Rathnayake; Sang-Cheol Bae; Zhanguo Li; Shereen Oon; Vera Golder; Mandana Nikpour; Masayoshi Harigai; Zhuoli Zhang; Eric Morand; Chak Sing Lau; Worawit Louthrenoo; Alberta Hoi; et al. (Lupus Science and Medicine)
Objective To estimate the prevalence of organ damage (damage) and flare and to examine longitudinal associations between flares and subsequent damage accrual, in patients with systemic lupus erythematosus (SLE).Methods Patients enrolled in the Asia Pacific Lupus Collaboration cohort with ≥3 years of prospectively captured data were studied. Flares were assessed at routine visits, while damage ((Systemic Lupus International Collaborating Clinics/American College of Rheumatology) Damage Index) was assessed annually. Multivariable, multifailure survival analyses were carried out to quantify the association between flares and damage accrual.Results 1556 patients with SLE with a median (IQR) of 5.7 (3.9, 7.0) years of follow-up were studied. 39.5% (n=614) of patients had damage at enrolment, and 31.9% (n=496) accrued damage during the study observation period. The incidence of damage accrual during observation was ~58/1000 person-years. Overall, 74.1% (n=1153) of patients experienced a flare of any severity (mild/moderate or severe) at least once; 56.9% (n=885) experienced recurrent (≥2) flares. The risk of subsequent damage accrual in patients who experienced mild-to-moderate flare, after controlling for confounders, was 32% greater than in patients without flares (adjusted HR) (95% CI 1.32 (1.17 to 1.72)). The risk of damage accrual was greater if patients had severe flares (HR (95% CI) 1.58 (1.18 to 2.11)). For each additional flare, the risk of damage accrual increased by 7% (HR (95% CI) 1.07 (1.02 to 1.13)).Conclusions Flares independently increased the risk of damage accrual. Prevention of flares should be considered a necessary goal of SLE disease management to minimise permanent damage.